Objections to Christian belief - MacKinnon, Donald MacKenzie, 1913-1994 (London. UK Constable, 1963)
Contents : Moral objections / by D.M. MacKinnon ; Psychological objections / by H.A. Williams ; Historical objections / by A.R. Vidler ; Intellectual objections by J.S. Bezzant
"Course of lectures...given in Cambridge in February 1963 under the auspices of the Divinity Faculty".
Keywords: Apologetics -- 20th century